2016
DOI: 10.1080/10245332.2016.1258152
|View full text |Cite|
|
Sign up to set email alerts
|

The role of long noncoding RNA HOTAIR in the acquired multidrug resistance to imatinib in chronic myeloid leukemia cells

Abstract: LncRNA HOTAIR modulates CML cell MDR in a PI3K/Akt-dependent way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 36 publications
1
43
0
1
Order By: Relevance
“…Next, we detected several known lncRNAs involved in drug resistance in K562 and K562/ADM cells by qRT-PCR, such as HOTAIR [28], PVT1 [29], H19 [10], MALAT1 [30], UCA1 [11], CCAL [31], ANRIL [32], MEG3 [33] and FENDRR [12]. Interestingly, we found that FENDRR was mostly downregulated in K562/ADM cells compared with that in K562 cells ( Fig.…”
Section: Lncrna Fendrr Level Was Downregulated In Adriamycin-resistanmentioning
confidence: 86%
“…Next, we detected several known lncRNAs involved in drug resistance in K562 and K562/ADM cells by qRT-PCR, such as HOTAIR [28], PVT1 [29], H19 [10], MALAT1 [30], UCA1 [11], CCAL [31], ANRIL [32], MEG3 [33] and FENDRR [12]. Interestingly, we found that FENDRR was mostly downregulated in K562/ADM cells compared with that in K562 cells ( Fig.…”
Section: Lncrna Fendrr Level Was Downregulated In Adriamycin-resistanmentioning
confidence: 86%
“…In addition, activation of the PI3K/ Akt signaling pathway was markedly reduced when the HOTAIR gene was silenced in K562-imatinib cells. These findings indicate that knockdown of HOTAIR played a crucial role in improving acquired resistance to imatinib in CML K562-R cells via the PI3K/Akt pathway [146]. Overall, although HOTAIR was involved in the development and progression of this type of malignancy and was associated with a poor clinical-pathologic prognostic stratification, the exact function and mechanism have yet to be elucidated.…”
Section: Hotair In Diffuse Large B-cell Lymphoma and Chronic Myelogenmentioning
confidence: 93%
“…Whole cell lysates were prepared in RIPA buffer containing protease inhibitors and western blotting was performed as described previously . Protein concentrations were measured using a protein assay kit (Pierce, Thermal Fisher, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%